DEIKSIS DALAM BAHASA TOMBULU - Louisa Rina Moningka (Kadera Bahasa, 2020)
AbstractThe purpose of this study is to describe the form and function of tombulu language deixis. This research is qualitative with descriptive method especially in collecting data scientifically, and producing linguistic rules in linguistics. Data for analysis need are sourced from the field and literature. Field data is collected through informants, and library data is taken from books. Data collection techniques used direct observation techniques, tapping records, notes, and interviews. For data analysis, the inductive method is adopted. The results of this study indicate that in terms of the form of tombulu language deixis can be in the form of a morpheme, a word and a phrase. In terms of function depends on the type of deixis. In tombulu only one form of deixis refer to him male and female. Deixis to designate a place in tombulu is known for three distinctions. While the possessive contructive of tombulu language is stick-right. In the syntactic distribution, the possessive construct of the tombulu language stick-right morpheme, clearly showing the characteristics of a consistent VO type language. Through deixis pointing in Tombulu language can answer Frei’s hypothesis, which says that the higher the level of culture, the simpler the language deictic system concerned. In the case of Tombulu language deixis especially the place deixis can reflect the low level of Tombulu culture. Keywords : deixis, Tombulu, language